Policy Innovation Strategies of Local Government to Enhance Regional Competitiveness: A Study in Jayapura City, Papua Province - Untung Muhdiarta; Muliadi Anangkota; Ilham Ilham; Djoko Susanto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Regional competitiveness in the era of global economic competition increasingly depends on the capacity of local governments to implement policy innovations. In Jayapura City, such innovations are crucial to overcome structural constraints and to optimize the potential of regional development. This study aims to examine the policy innovation strategies implemented by the Jayapura City Government, identify supporting and inhibiting factors, and assess their contribution to economic growth, human resource quality improvement, and investment climate enhancement. Employing a qualitative case study approach, the research involved in-depth interviews, field observations, and policy document reviews. Key informants included local government officials, micro, small, and medium enterprise (MSME) actors, academics, and community leaders. The findings indicate that the digitalization of licensing services, the establishment of the Regional Innovation Forum, and human resource training programs have positively impacted public service efficiency, ease of doing business, and cross-sector collaboration. However, challenges such as limited digital literacy, uneven infrastructure development in peripheral areas, and a shortage of innovative human resources still hinder policy optimization. Overall, the policy innovations of the Jayapura City Government have contributed to strengthening regional competitiveness, but their sustainability requires strategies to ensure equitable benefits, enhance human resource capacity, and maintain consistent data-driven evaluation.